FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TINDAKAN PENGHINDARAN PAJAK PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - yuni, Sri Wah (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2022)
This study aims to find empirical evidence regarding the factors that influence tax avoidance in coal mining sub-sector companies listed on the Indonesia Stock Exchange. The factors tested in this study are capital intensity, audit quality and independent board of commissioners. The sample in this study used 12 coal mining sub-sector companies listed on the Indonesia Stock Exchange for the period 2015-2019 which were taken using purposive sampling. These factors were then tested by multiple linear regression at a significance level of 5 percent. The results of this study identify that capital intensity has a significant positive effect on tax avoidance in coal mining sub-sector companies listed on the Indonesia Stock Exchange. Audit quality has a significant negative effect on tax avoidance in coal mining sub-sector companies listed on the Indonesia Stock Exchange. The independent board of commissioners has no effect on tax evasion in coal mining sub-sector companies listed on the Indonesia Stock Exchange. Keywords : Tax Avoidance, Capital Intensity, Audit Quality and Independent Board of Commissioner.